Joshua Z. answered • 08/28/12

Experienced, Excellent Tutor - My Record Speaks For Itself

This question is slightly hard to read due to a lack of parentheses, but I believe the question is:

-2x + 5 = -x

x+6 x+6

The easiest way to solve this is to add x/(x+6) to both sides, leaving:

-x + 5 = 0

x+6

Then subtract 5 from each side of the equation, and multiply each side by x+6:

-x = -5(x+6)

Multiplying each side by -1 (to make it simpler) and distributing the 5 leaves you with:

x = 5x + 30

Subtract 5x from each side to arrive at:

-4x = 30

Finally, divide each side of the equation by -4 to arrive at your answer:

x = -7.5

You can check this answer by plugging x back into the original equation, like so:

-2(-7.5) + 5 = -(-7.5)

(-7.5)+6 (-7.5)+6

(15/-1.5) + 5 = (7.5/-1.5)

-10 + 5 = -5

-5 = -5